تقييم تجربة التّحول للعمل المصرفي الإسلامي عن طريق مدخل الفروع الإسلامية - المصرف السّعودي الفرنسي أنموذجً ا-: Evaluation of the experience of converting to Islamic banking through the entrance of Islamic branches -The Saudi French Bank as a model– - بن عبد الرحمان البشير; شرفة حكيمة (Journal of North African Economies, 2025)
This study aimed to shed light on the traditional Saudi French bank in its transformation into Islamic banking by adopting the approach of Islamic branches, which means the Islamization of branch operations in terms of resources and uses in its first axis, and to stand on the financial developments that the bank knew after its transformation in the Second axis, and to identify the effects of this transformation on the liquidity, profitability and activity of the bank in the third axis. The study reached many results, the most important of which are: that there are fundamental differences in the average ratios of liquidity, profitability, and activity of the Saudi French Bank before and after the transformation.